An environmentally friendly solvent mix for asphaltene deposit removal - Elochukwu, Okafor; Ben Mahmud, Hisham (Asian Research Publishing Network (A R P N), 2015)
© 2006-2015 Asian Research Publishing Network (ARPN). Conventional benzene, toluene and xylene (BTX) solvents have been successfully applied for remediation of asphaltene problems during crude oil production and processing. However, BTX solvents have low flash point, high acute toxicity and low biodegradability, and therefore, considered non-environmentally friendly. Consequently, stringent environmental laws are continuously enacted to restrict the applications of such solvents. This paper investigates the utilization of environmentally benign solvents derived from natural and renewable precursors to dissolve and disperse asphaltene deposits. A composite mixture of methyl ester oleate and ethanol was examined in a solvent and co-solvent synergistic function to dissolve and disperse asphaltene. The solvent blend possesses favourable health, safety and environmentally friendly characteristics such as high flash point (78°C) and high biodegradability (98%). Results show that the composite solvent gives better dissolution and dispersion of asphaltene deposits when compared with the respective performance of methyl ester oleate and aromatic xylene. Further adsorption studies was conducted and experimental data validated by Langmuir and Freundlich models, confirms a favourable adsorption of methyl ester oleate and methyl ester oleate/ethanol mix on asphaltene.